Pengaruh Variasi Konsentrasi NaOH Sebagai Alkali Aktivator Terhadap Kuat Tekan Semen Geopolimer Berbasis Tanah Napa - Aufa Rahmi; Mawardi Mawardi (Departemen Kimia FMIPA UNP, 2022)
In 1970, Davidovits had discovered an alternative binder called geopolymer. Geopolymers provide a solution to the disadvantages of Portland cement which are not environmentally friendly. Geopolymer is a material or binder material that is synthesized by mixing alumina silicate source material and alkaline activator solution. One of them is Napa land. Napa soil contains high levels of SiO2 and Al2O3 with percentages of 62.70% and 31.16% based on XRF test. NaOH solution mixed with Na2SiO3 was used as an activator whose concentration was varied from 8M to 14M. The ratio of the weight of Na2SiO3 to the weight of the NaOH solution is 1.5. The characteristics of the geopolymer cement based on napa soil showed that the analysis of optimum compressive strength was achieved at a concentration of 14M. Compressive strength test of cylindrical specimens, splitting test and porosity test were carried out comprehensively to compare the specimens from each composition. The higher the concentration of NaOH,the higher the compressive strength produced.